Assessing Alzheimer's disease patients' quality of life: Discrepancies between patient and caregiver perspectives. Issue 4 (23rd October 2015) - Andrieu, Sandrine; Coley, Nicola; Rolland, Yves; Cantet, Christelle; Arnaud, Catherine; Guyonnet, Sophie; Nourhashemi, Fati; Grand, Alain; Vellas, Bruno; ,
Abstract: Introduction: Quality of life (QOL) is an important dimension to consider in Alzheimer's disease (AD), but few large‐scale studies have analyzed self and caregiver reports of patient QOL. Methods: Patient QOL was evaluated in a cohort of 574 AD patients with the QOL‐AD scale over 2 years. Results: Caregiver reports of patient QOL were lower at baseline than self reports. Older patient age was associated with overestimation of QOL by caregivers, whereas neuropsychiatric inventory score and caregiver burden were associated with underestimation. Activities of daily living limitation, depressive symptoms, and caregiver burden were systematically associated with poorer QOL, whereas caregiver relationship and apathy were associated with poorer QOL only for self reports or caregiver reports, respectively. Cognitive function and professional care were not associated with QOL. Self‐rated patient QOL did not change over time, whereas disease severity markers and caregiver‐rated patient QOL declined. Discussion: It is important to assess both self and caregiver ratings when assessing patient QOL.